(3GdSdhc GdJcjai dOi GdGWaGd Phi UYhHGJ GdJYde HOhdJi eUQ hGdGeGQGJ (B: s (3OQGSI YHQ KbGajI (B/ s - (3CTQa CMeO Ydi ZRGd s; (3SgjQ cGed CMeO (B: s; (3eMehO YHOGdMdje efSi (B: s ((3GdbGgQI (B: s (3CTQa CMeO Ydi ZRGd (B: s, 2007)
(3JgOa GdOQGSI Gdi GdHMK ai GdSdhc GdJcjai dOi Phi UYhHGJ GdJYde hPdc ef NdGd ebGQfJge H GbQGfge ef GdGWaGd GdYGOjjf ceG JgOa GdOQGSI GjVG Gdi GdcTa Yf GKQ eJZjQi GdHjFI hGdLfS Ydi GdSdhc GdJcjai ddGWaGd Phi UYhHGJ GdJYde hef Ke GdJhUd Gdi HYV GdJWHjbGJ GdJQHhjI GdJi JSGYO ai QYGjI gDdGA GdGWaGd hHGdfXQ Gdi Gf GdbjeI GdfgGFjI dfJGFL GdJQHjI Jcef ai eOi edGAeI eG JYdeI GdaQO dMGLGJ JcjaI eY GdMjGI heY eJWdHGJ GdeLJeYs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI QjGV GdGWaGd (B- (3bSe GdYdhe GdfaSjIs
Keywords: (3GdGWaGd Phi UYhHGJ GdJYdes; (3GdSdhc GdJcjais; (3eUQ hGdGeGQGJs